The construction of the attitude scale toward independent journalism - Klišanin, Martina; Sindik, Joško (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2015)
Systematization of the attitudes toward independent journalism may allow researchers to explore this issue in a relatively systematic way, in a particular spatial and temporal context, correlating it with the factors that can help us to understand attitudes towards this issue more clearly, and possibly change them. The main objective of this research was to construct an attitude scale toward independent journalism. Furthermore, we tried to gain insight into the structure of these attitudes and to determine whether there were significant differences in attitudes with regard to gender, education and region of origin of the participants, as well as the connection between attitudes to the age of the participants. Also, we have found differences in the beliefs about certain types of media, compared to the same independent variables. The sample in the study was covenient, consisted of a total of 83 participants, of whom 35 men (42%) and 48 women (58%). The results showed that the Attitude scale toward independent journalism has been successfully designed, with two principal components that have demonstrated satisfactory reliability: Dependence on finances and the inability of independent journalism and Sensationalism and being controlled. The only statistically significant difference reflects the fact that higher educated participants more often believe that journalists are dependent on finances and that there is no possibility of independent journalism, while the most educated group of participants with at least agrees with such attitude. All groups of participants equally (do not) believe all types of media.
Keywords: independent journalism; sensationalism; public relations; Objectivity